PENGEMBANGAN KOMIK DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR AKUNTANSI DASAR KELAS X AKUNTANSI DI SMK X - Liana Fahrunisa; Sri Sumaryati; Lies Nurhaini (Universitas Sebelas Maret, 2022)
Abstract This study aims to determine the procedure for developing accounting digital comics learning media. The accounting digital comic learning media will be developed at SMK X in class X Accounting. This research is an R&D (Research & Development) research using the ADDIE development model with 5 stages of Analysis, Design, Development or Production, Implementation or Delivery and Evaluation. The data sources of this research include learning events, informants (basic accounting teachers and students of class X AK I and II) and documents (syllabus, lesson plans). The results of the study are at the analysis stage, the use of learning media has not been maximally utilized by teachers and students in achieving learning objectives. In the design stage, teachers need learning media in the form of learning videos and students like media in the form of videos that have many colors and images, so that the Digital Accounting Comics media will be developed. In the development stage, the media is declared suitable for use. This is evidenced by the assessment of media experts by 84%, from material experts by 87%, and from educators by 87%. In the implementation phase, the results of one-on-one trials are 95%, and the results of small group trials are 92%. The results of this study conclude that digital accounting comics are suitable for use in accounting learning. Keywords: digital comics, accounting learning, learning media Abstrak Penelitian ini bertujuan untuk mengetahui prosedur pengembangan media pembelajaran komik digital akuntansi. Media pemebelajaran komik digital akuntansi tersebut akan dikembangkan di SMK X pada kelas X Akuntansi. Penelitian ini merupakan penelitian R&D (Research & Development) dengan menggunakan model pengembangan ADDIE dengan 5 tahapan Analysis, Design, Development or Production, Implementation or Delivery and Evaluation. Sumber data penelitian ini meliputi peristiwa pembelajaran, informan (guru akuntansi dasar dan siswa kelas X AK I dan II) dan dokumen (silabus, RPP). Hasil penelitian adalah pada tahap analisis, penggunaan media pembelajaran belum maksimal dimanfaatkan guru dan siswa dalam pencapaian tujuan pembelajaran. Tahap desain, guru membutuhkan media pembelajaran berupa video pembelajaran dan peserta didik menyukai media yang berbentuk video yang memiliki banyak warna dan gambar, sehingga media komik digital akuntansi akan dikembangkan. Tahap pengembangan, media dinyatakan layak untuk digunakan. Hal ini dibuktikan penilaian dari ahli media sebesar 84%, dari ahli materi sebesar 87%, dan dari pendidik sebesar 87%. Tahap implementasi, hasil uji coba satu -satu sebesar 95%, dan hasil uji coba kelompok kecil sebesar 92%. Hasil penelitian ini menyimpulkan bahwa komik digital akuntansi layak digunakan dalam pembelajaran akuntansi. Kata Kunci: komik digital, pembelajaran akuntansi, media pembelajaran